A waste lithium iron phosphate material recycling process and sodium iron phosphate-based positive electrode material
By optimizing the recycling process of waste lithium iron phosphate materials, using graded grinding, weak acid solution impregnation of lithium and hot-saturated sodium carbonate solution to supplement sodium, a sodium iron phosphate-based positive electrode material with a core-shell structure is formed, which solves the cumbersome and environmental pollution problems in the recycling process of waste lithium iron phosphate batteries, and achieves efficient and low-cost resource recovery and improved electrochemical performance.
Patent Information
- Application Number
- CN202411570138.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
In the prior art, the full component recycling process of waste lithium iron phosphate batteries has problems such as cumbersome, high cost and harsh process conditions, and traditional methods may cause environmental pollution.
By optimizing the recycling process of waste lithium iron phosphate materials, using carbon source wetting agents and grading grinding, weak acid solution impregnation of lithium, and hot-saturated sodium carbonate solution to supplement sodium, forming an olivine-type sodium iron phosphate core material without inert phase, and forming a mixed carbon shell structure of sodium iron pyrophosphate on its surface to prepare a sodium iron phosphate-based positive electrode material with a core-shell structure.
It realizes efficient recycling of waste lithium iron phosphate materials, and prepares sodium iron phosphate-based positive electrode materials with excellent electrochemical properties and cycle stability, reducing the damage to the environment by resource mining and improving resource self-sufficiency.
Smart Images

Figure CN119069863B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium iron phosphate material recycling, and in particular relates to a waste lithium iron phosphate material recycling process and a sodium iron phosphate-based positive electrode material. Background Art
[0002] As a cathode material, lithium iron phosphate (LiFePO4) is highly favored in the field of lithium-ion batteries due to its many advantages. LiFePO4 batteries have high safety performance, long cycle life, good thermal stability and environmental friendliness, making them widely used in electric vehicles, energy storage systems and portable electronic devices. However, with the popularity of these devices, the treatment and recycling of waste lithium iron phosphate batteries has become increasingly prominent.
[0003] The recycling of used lithium iron phosphate batteries is not only an environmental issue, but also a resource issue. The reserves of lithium, iron, phosphorus and other metal elements contained in batteries are limited in nature and unevenly distributed. Therefore, recycling lithium, iron, phosphorus and other metal elements in used batteries is of great significance for improving resource self-sufficiency and reducing dependence on imports.
[0004] However, there are many technical difficulties in the current recycling process of lithium iron phosphate powder. These difficulties include cumbersome process, high cost and harsh process conditions. Traditional recycling methods often require complex chemical treatment processes, which not only consume a lot of energy and chemical reagents, but also may produce harmful by-products and cause secondary pollution to the environment.
[0005] In order to achieve efficient recycling of waste lithium iron phosphate batteries, researchers have proposed a variety of recycling technologies. Among them, hydrometallurgy is a common method, which uses chemical solutions to treat waste batteries, dissolves the valuable metal elements in them, and then separates and purifies these elements through chemical precipitation, solvent extraction or ion exchange. However, hydrometallurgy also has problems such as high cost, complex process and environmental pollution.
[0006] Another promising method is direct thermal treatment technology, which uses high temperatures to decompose organic matter in used batteries and convert inorganic matter into a form that is easier to recycle. The advantages of this method are relatively simple process and low energy consumption, but its disadvantages are that it may require a high initial investment cost and requires high heat resistance of the equipment.
[0007] In addition to the above technologies, researchers have also explored biometallurgy, which is to use the metabolism of microorganisms to recycle metal elements in batteries. This method has the advantages of low cost and environmental friendliness, but it is still in the laboratory research stage and is still a long way from practical application.
[0008] In short, with the continuous expansion of the application of lithium iron phosphate batteries, the recycling of waste batteries has become increasingly important. Developing a low-cost, high-efficiency and environmentally friendly full-component recycling method can not only reduce the demand for new resource mining and reduce the damage to the environment caused by resource mining, but also increase resource self-sufficiency and create economic value. Therefore, it is particularly urgent to develop a low-cost, high-efficiency and environmentally friendly full-component recycling method. Summary of the invention
[0009] In view of the problems in the prior art, the present invention discloses a waste lithium iron phosphate material recovery process and a sodium iron phosphate-based positive electrode material. The present invention optimizes the recovery process of waste lithium iron phosphate materials, sequentially adopts the methods of adding a carbon source impregnating agent and performing graded grinding, performing lithium immersion treatment through a weak acid solution, and combining with a hot saturated sodium carbonate solution to supplement sodium, so as to achieve the function of dual-construction materials, thereby facilitating the formation of an olivine-type sodium iron phosphate core material without an inert phase; after the carbon source impregnating agent is infiltrated and coated, a sodium source, a phosphorus source, and an iron source are combined to perform secondary coating on the surface of the sodium iron phosphate core material to form a sodium iron phosphate pyrophosphate mixed carbon shell structure, thereby preparing a sodium iron phosphate-based positive electrode material with a core-shell structure; and the sodium ion battery application field exhibits excellent electrochemical performance and cycle stability.
[0010] The present invention is achieved through the following technical solutions:
[0011] In a first aspect, the present invention provides a process for recycling waste lithium iron phosphate materials, the specific steps of which include:
[0012] S1: adding waste lithium iron phosphate powder material to pure water containing a carbon source impregnant, performing a first grinding with a grinding medium and filtering to remove ductile impurities to obtain a preliminary grinding slurry, wherein the average particle size of the powder in the preliminary grinding slurry is 1-3 μm; and the ductile impurity content meets 0%-0.3%;
[0013] S2: Grind the preliminary grinding slurry described in S1 for a second time through a grinding medium, and then filter to remove ductile impurities to obtain a secondary grinding slurry. At this time, the average particle size of the powder in the secondary grinding slurry is 0.05-0.8 μm. The secondary grinding slurry is tested for ductile impurity content to ensure that the ductile impurity content W meets 0-0.01% before proceeding to the next operation step; wherein, the ductile impurity content refers to the mass of the ductile impurities as a percentage of the mass of the measured slurry after drying;
[0014] S3: Add excess weak acid solution to the secondary grinding slurry in S2 to treat it, so that lithium is leached out. After solid-liquid separation, the solid phase material is added to excess hot saturated sodium carbonate solution to react and obtain sodium iron phosphate Na x FePO4; wherein x is selected from 0.9-1.05;
[0015] S4: Mix the sodium source, phosphorus source, iron source and the sodium iron phosphate Na described in S3 x FePO4 was mixed to prepare a sodium iron phosphate-based positive electrode precursor material;
[0016] S5: heat treating the sodium iron phosphate-based positive electrode precursor material described in S4 under an inert gas atmosphere to obtain a sodium iron phosphate-based positive electrode material;
[0017] As a further solution, the amount of the carbon source wetting agent added in S1 accounts for 0.2%-1% of the amount of the waste lithium iron phosphate powder material added, and the amount of the waste lithium iron phosphate powder material added in S1 accounts for 20%-40% of the mass of the pure water.
[0018] As a further solution, the average particle size of the powder in the secondary grinding slurry in S2 is preferably in the range of 0.05-0.1 μm.
[0019] As a further solution, the ductile impurities include one or more metal elements selected from Cu, Al, Sn, S, Ni, and Co; the ductile impurities are mainly Al and Cu, so W in S3 is the percentage of the Al and Cu ductile impurity content in the mass of the slurry after drying.
[0020] As a further solution, the carbon source wetting agent in S1 includes one or more of sodium carboxymethyl cellulose, sodium lignin sulfonate, and sodium dodecyl sulfate.
[0021] As a further solution, the grinding media in S1 and S2 include one or more of tungsten steel grinding media, cemented carbide grinding media, ceramic grinding media, and glass grinding media; as some specific examples: the cemented carbide grinding media include one or more of tungsten carbide-based cemented carbide and titanium carbide-based cemented carbide; the ceramic grinding media include one or more of zirconium oxide and aluminum oxide.
[0022] Preferably, the grinding media in S1 and S2 are preferably ceramic grinding media.
[0023] As a further solution, the diameter of the grinding medium in S1 is greater than the diameter of the grinding medium in S2; the mesh size of the filter screen in S1 is less than the mesh size of the filter screen in S2; the grinding time in S1 and S2 is 10-30 minutes;
[0024] Preferably, the diameter of the grinding medium in S1 is 0.8-1.5 mm, and the mesh size of the filter screen is 100-200 meshes; the diameter of the grinding medium in S2 is 0.1-0.7 mm, and the mesh size of the filter screen is 300-500 meshes.
[0025] As a further solution, the molar ratio of elements in the sodium iron phosphate-based positive electrode precursor material in S4 is selected from Na:Fe:P 3-y:2:3; y=0~0.01.
[0026] As a further solution, the weak acid solution in S3 is selected from one or more of carbonic acid, carboxylic acid, acetic acid, and citric acid.
[0027] As a further solution, the molar mass N of the hot saturated sodium carbonate solution in S3 is selected from N>0.7n; n is the molar mass of the waste lithium iron phosphate powder material.
[0028] As a further solution, the solid-liquid separation method in S3 includes one or more of centrifugal separation, vacuum filtration, pressure filtration, and ultrafiltration.
[0029] As a further solution, the preparation method in S4 is one or more of spray drying, freeze drying, and sol-gel method.
[0030] Preferably, the preparation method in S4 is preferably a spray drying method.
[0031] As a further scheme, the sodium source in S4 is selected from one or more of sodium carbonate, sodium acetate, sodium citrate, sodium oxalate, and sodium bicarbonate; the iron source is selected from one or more of ferric phosphate, ferric chloride, ferric nitrate, and ferric sulfate; the phosphorus source is one or more of phosphoric acid, ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
[0032] As a further solution, the inert atmosphere in S5 is selected from one of argon and nitrogen atmospheres.
[0033] As a further solution, the heat treatment method in S5 is to undergo two heat treatment steps, the first heat treatment temperature is selected from 200-400°C, and the heat treatment time is selected from 1 to 5 hours; the second heat treatment temperature is selected from 600 to 800°C, and the heat treatment time is selected from 5 to 10 hours; the heating rate is selected from 5 to 10°C / min.
[0034] In a second aspect, the present invention provides a sodium iron phosphate-based positive electrode material, which is prepared by recycling the waste lithium iron phosphate material recycling process described in the first aspect.
[0035] In a third aspect, the present invention provides a sodium iron phosphate-based positive electrode plate, wherein the positive electrode plate comprises the sodium iron phosphate-based positive electrode material of the second aspect, a conductive agent and a binder as described in the present invention.
[0036] The present invention has no particular restrictions on the type of conductive agent, as long as it has the function of enhancing the conductivity of the negative electrode and does not adversely affect the performance of the sodium iron phosphate-based positive electrode material. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As some specific examples, the conductive agent used to prepare the negative electrode plate can be selected from carbon blacks such as acetylene black and conductive carbon black, conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, polythiophene, tin oxide, zinc oxide and other metal oxide conductive agents and carbon nanofiber conductive agents, etc.
[0037] The present invention does not particularly limit the type of binder, as long as it has the effect of enhancing the adhesion between the negative electrode active material particles and does not adversely affect the performance of the sodium iron phosphate-based positive electrode material. Those skilled in the art can choose according to actual needs. As some specific examples, the binder used to prepare the negative electrode plate includes polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyimide, polystyrene sulfonic acid, polyacrylonitrile, polycarbonate or polyetherimide ketone, etc.
[0038] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte described in the third aspect.
[0039] The characteristics and beneficial effects of the present invention are:
[0040] (1) The present invention adopts graded grinding technology and adds a carbon source impregnating agent to effectively remove ductile impurities mainly composed of aluminum and copper; at the same time, an optimized particle size distribution is achieved, which is conducive to the embedding of lithium ions and expands the ion transmission channel, which is convenient for the subsequent reaction with a hot saturated sodium carbonate solution to supplement sodium, thereby improving the stable embedding effect of sodium ions and providing a good prerequisite for the synthesis of an olivine-type sodium iron phosphate core material; at the same time, a carbon source is provided to maintain the stability of the structure and enhance the conductivity.
[0041] (2) The present invention uses an acidic solution to perform lithium ion embedding treatment, and combines it with a hot saturated sodium carbonate solution to supplement sodium ions, thereby achieving the dual construction purpose of the material, further expanding the ion transmission channel, and facilitating the formation of an olivine-type sodium iron phosphate core material without an inert phase; and after the carbon source impregnating agent is infiltrated and coated, it is combined with a sodium source, a phosphorus source, and an iron source for secondary coating, forming a sodium iron phosphate pyrophosphate mixed carbon shell structure on the surface of the sodium iron phosphate core material, thereby preparing a sodium iron phosphate-based positive electrode material Na with a stable core-shell structure. x FePO4@Na2FeP2O7&C; In the application field of sodium-ion batteries, this material exhibits excellent electrochemical performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0043] Figure 1 This is a SEM image of the waste lithium iron phosphate powder material in Example 1.
[0044] Figure 2 This is a SEM image of the solid phase after the lithium immersion treatment with the citric acid solution in Example 1 is completed.
[0045] Figure 3 This is a SEM image of the sodium iron phosphate-based positive electrode material product in Example 1.
[0046] Figure 4 This is the XRD diagram of the sodium iron phosphate-based positive electrode material product in Example 1.
[0047] Figure 5 This is the XRD diagram of the sodium iron phosphate core structure in Example 1.
[0048] Figure 6 is the electrochemical performance diagram of the sodium iron phosphate-based positive electrode material in Example 1, wherein Figure 6 A is the reversible specific capacity test diagram of the product, Figure 6 B is the 1C cycle retention rate diagram of the product, Figure 6 C is the rate capacity diagram of the product at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, and 20C.
[0049] Figure 7 is the electrochemical performance diagram of the sodium iron phosphate-based positive electrode material in Example 7, wherein Figure 7 A is the reversible specific capacity test diagram of the product, Figure 7 B is the 1C cycle retention rate diagram of the product, Figure 7 C is the rate capacity diagram of the product at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, and 20C.
[0050] Figure 8 This is the electrochemical performance diagram of the sodium iron phosphate-based positive electrode material in Comparative Example 2, where Figure 8 A is the reversible specific capacity test diagram of the product, Figure 8 B is the 1C cycle retention rate diagram of the product, Figure 8 C is the rate capacity diagram of the product at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, and 20C. DETAILED DESCRIPTION
[0051] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0052] The present invention has explored and studied the recycling process of waste lithium iron phosphate materials, and the present invention has found that sodium iron phosphate (NaFePO4), as a material with a similar crystal structure to lithium iron phosphate (LiFePO4), has unique advantages in electrochemical performance, and is even superior to lithium iron phosphate in some aspects, such as higher charge and discharge efficiency and longer cycle life. In addition, due to the abundant and low price of sodium resources, sodium iron phosphate also has obvious advantages in cost. Therefore, the present invention has conducted a series of experimental studies, hoping to efficiently recover the lithium iron phosphate metal element while directly preparing it into a sodium iron phosphate-based positive electrode material to achieve sustainable development of resources.
[0053] In a first aspect, the present invention provides a process for recycling waste lithium iron phosphate materials, the specific steps of which include:
[0054] S1: adding waste lithium iron phosphate powder material to pure water containing a carbon source impregnant, performing a first grinding with a grinding medium and filtering to remove ductile impurities to obtain a preliminary grinding slurry, wherein the average particle size of the powder in the preliminary grinding slurry is 1-3 μm; and the ductile impurity content meets 0%-0.3%;
[0055] S2: Grind the preliminary grinding slurry described in S1 for a second time through a grinding medium, and then filter to remove ductile impurities to obtain a secondary grinding slurry. At this time, the average particle size of the powder in the secondary grinding slurry is 0.05-0.8 μm. The secondary grinding slurry is tested for ductile impurity content to ensure that the ductile impurity content meets 0-0.01% before proceeding to the next operation step; wherein the ductile impurity content refers to the percentage of the mass of the ductile impurities to the mass of the measured slurry after drying;
[0056] S3: Add excess weak acid solution to the secondary grinding slurry in S2 to treat it, so that lithium is leached out. After solid-liquid separation, the solid phase material is added to excess hot saturated sodium carbonate solution to react and obtain sodium iron phosphate Na x FePO4; wherein x is selected from 0.9-1.05;
[0057] S4: Mix the sodium source, phosphorus source, iron source and the sodium iron phosphate Na described in S3 x FePO4 was mixed to prepare a sodium iron phosphate-based positive electrode precursor material;
[0058] S5: heat treating the sodium iron phosphate-based positive electrode precursor material described in S4 under an inert gas atmosphere to obtain a sodium iron phosphate-based positive electrode material;
[0059] First, the present invention adds waste lithium iron phosphate powder material into pure water containing carbon source impregnating agent for graded grinding. In the process of preliminary grinding of waste lithium iron phosphate powder material, when the particle size reaches a specific range (1-3 μm), it can ensure that the waste lithium iron phosphate material is fully broken, and at the same time, the ductile impurities are exposed, which is convenient for aggregation and removal by filtration during the preliminary grinding process. In addition, this also helps to prevent the generation of too small particles in the early stage of grinding, thereby preventing impurities from being ground together and mixed in, affecting the aggregation of ductile impurities. The powder material is further refined through secondary grinding to ensure that the particle size reaches a smaller range (0.05-0.8μm); on the one hand, the residual ductile impurities are fully removed, and the impurity content is ensured to meet the qualified standard through the ductile impurity content test; on the other hand, the predetermined powder particle size is obtained through secondary grinding, which is conducive to the smooth leaching of lithium elements in the subsequent process. The optimized range of powder particle size is also convenient for widening the ion transmission channel during the acid treatment lithium leaching process, thereby improving the stable embedding effect of sodium ions when reacting with hot saturated sodium carbonate solution to supplement sodium, and providing a good prerequisite for the synthesis of sodium iron phosphate core materials with olivine structure; in addition, the secondary grinding fully opens the carbon coating layer on the surface of the waste lithium iron phosphate material, and also helps to achieve the effect of sufficient lithium leaching using only weak acid when using acid solution for lithium leaching operation, thereby maintaining the structural stability of the material.
[0060] Secondly, the present invention also adds a carbon source wetting agent during graded grinding. On the one hand, the wetting agent can be used to improve the wettability between the waste lithium iron phosphate powder material and the aqueous solution, ensure that the agglomerated particle size is fully opened, and effectively remove the ductile impurities mainly composed of Al and Cu; on the second hand, the wetting agent, as a carbon source, improves the wetting effect while providing a carbon source for the subsequent formation of the sodium iron pyrophosphate shell structure, and fully disperses the carbon source during the graded grinding process to form a uniform and dense conductive layer, thereby improving the conductivity of the sodium iron phosphate-based positive electrode material with a core-shell structure; on the third hand, the fully dispersed carbon source can be well combined with the powder particle size within a predetermined range after graded grinding, which is helpful to maintain the stable existence of the olivine structure of the sodium iron phosphate core material during the subsequent acid treatment lithium immersion and hot saturated sodium carbonate solution sodium supplementation, and avoid the generation of inert phase impurities during the reaction process, thereby ensuring that the final sodium iron phosphate-based positive electrode material has good electrochemical properties.
[0061] In addition, the present invention uses a weak acid solution to immerse the high-purity solid phase material obtained after double grinding into lithium. On the one hand, during the acid treatment and lithium immersion, it can cause slight etching on the surface of the material, maintain structural stability, enable the smooth escape of lithium ions, and fully recover lithium metal in the form of lithium salts. On the other hand, while the weak acid solution promotes the smooth escape of lithium ions, the vacancies formed by it further broaden the ion transmission channel, which is helpful to improve the smooth adsorption and embedding of sodium ions when reacting with a hot saturated sodium carbonate solution to supplement sodium, thereby forming a sodium iron phosphate core material with a stable olivine structure.
[0062] Finally, in the process of recycling waste lithium iron phosphate powder materials to prepare sodium iron phosphate-based positive electrode materials, the present invention uses hot saturated sodium carbonate solution to provide a sodium source and recombine with the phosphorus-iron framework to form a sodium iron phosphate core material with an olivine structure without an inert phase; the residual weak acid solution can also be removed when dissolving the solid phase material to avoid the adverse effect of the residual weak acid solution on the formation of the sodium iron phosphate core material with an olivine structure without an inert phase; in addition, when the residual weak acid solution is removed, the generated CO2 gas can expand the crystalline structure gap, thereby further widening the ion transmission channel under the dual construction effect of the weak acid solution and the CO2 gas, improving the structural stability, and forming a sodium iron phosphate core material with a stable olivine structure after the sodium supplementation reaction of the saturated sodium carbonate solution; at the same time, the carbon source wetting agent is infiltrated and coated, and the sodium source, phosphorus source, and iron source are combined for secondary coating, and a sodium iron phosphate pyrophosphate mixed carbon shell structure is formed on the surface of the sodium iron phosphate core material by heat treatment, thereby preparing a sodium iron phosphate-based positive electrode material Na with a core-shell structure. x FePO4@Na2FeP2O7&C. This material has both a stable olivine core structure and a sodium iron phosphate pyrophosphate mixed carbon shell structure with better conductivity, which can show excellent electrochemical performance and cycle stability in the application field of sodium ion batteries.
[0063] As a further solution, the amount of the carbon source wetting agent added in S1 accounts for 0.2%-1% of the amount of the waste lithium iron phosphate powder material added, and the amount of the waste lithium iron phosphate powder material added in S1 accounts for 20%-40% of the mass of the pure water.
[0064] The addition amount of carbon source wetting agent and waste lithium iron phosphate powder material within the appropriate range can, on the one hand, ensure that the material is fully crushed during the grinding process, while avoiding agglomeration caused by excessive carbon source wetting agent, thereby improving the grinding efficiency and the uniformity of the lithium iron phosphate material; on the other hand, it is beneficial to effectively remove impurities during the graded grinding process and evenly disperse them in the waste lithium iron phosphate powder material, which is beneficial to obtain a sodium iron phosphate-based positive electrode material with a core-shell structure after heat treatment, thereby preparing a battery material with excellent electrochemical properties.
[0065] As a further solution, the average particle size of the powder in the secondary grinding slurry in S2 is preferably from 0.05 to 0.1 μm; the average particle size of the powder within the preferred range helps to more smoothly leach lithium ions, while ensuring that the ion transmission channel is unobstructed during the subsequent sodium ion embedding process, thereby improving the electrochemical properties of the material. In addition, a smaller powder particle size helps to form a more uniform and dense core-shell structure during the heat treatment process, further enhancing the conductivity and structural stability of the material.
[0066] As a further solution, the ductile impurities include one or more metal elements selected from Cu, Al, Sn, S, Ni, and Co; the ductile impurities are mainly Al and Cu, so W in S3 is the percentage of Al and Cu ductile impurity content in the mass of the dried slurry. Ductile metal impurities have good ductility and are prone to deformation rather than fracture when subjected to external forces during the grinding process, so they can be separated and removed by filtering and crushing waste lithium iron phosphate powder materials; the ductile impurities come from the positive active material, negative active material, conductive agent, binder, electrolyte or metal foil, current collector, diaphragm, etc. in the battery; in general, the ductile impurities are mainly Al and Cu from the current collector.
[0067] As a further solution, the carbon source wetting agent in S1 includes one or more of sodium carboxymethyl cellulose, sodium lignin sulfonate, and sodium dodecyl sulfate. The type of wetting agent used in the present invention is not only conducive to improving the wettability of waste lithium iron phosphate powder materials, fully crushing waste lithium iron phosphate powder materials, and improving impurity removal efficiency, but also in the subsequent preparation process of sodium iron phosphate-based positive electrode materials, it can participate in the reaction as a carbon source to form a conductive network, thereby improving the electrochemical performance of the material.
[0068] As a further solution, the grinding media in S1 and S2 include one or more of tungsten steel grinding media, cemented carbide grinding media, ceramic grinding media, and glass grinding media; as some specific examples: the cemented carbide grinding media include one or more of tungsten carbide-based cemented carbide and titanium carbide-based cemented carbide; the ceramic grinding media include one or more of zirconium oxide and aluminum oxide.
[0069] Preferably, the grinding media in S1 and S2 are preferably ceramic grinding media; the ceramic grinding media has good chemical stability and strong corrosion resistance, can fully crush the waste lithium iron phosphate powder material, and will not introduce additional metal impurities during the grinding process, thereby ensuring the high recovery rate of waste lithium iron phosphate materials and the purity and quality of the final product sodium iron phosphate-based positive electrode material.
[0070] As a further solution, the diameter of the grinding medium in S1 is greater than the diameter of the grinding medium in S2; the mesh size of the filter screen in S1 is less than the mesh size of the filter screen in S2; the grinding time in S1 and S2 is 10-30 minutes;
[0071] Preferably, the diameter of the grinding medium in S1 is 0.8-1.5 mm, and the mesh size of the filter screen is 100-200 meshes; the diameter of the grinding medium in S2 is 0.1-0.7 mm, and the mesh size of the filter screen is 300-500 meshes.
[0072] The use of relatively large diameter grinding media and large mesh filter in S1 of the present invention can ensure that the waste lithium iron phosphate powder material is fully broken during the initial grinding process, while retaining larger ductile impurity particles for subsequent filtration and separation. The use of relatively small diameter grinding media and small mesh filter in S2 is to further refine the particles, remove ductile impurities in the waste lithium iron phosphate powder material, ensure the improvement of grinding efficiency and purity of the secondary grinding slurry, and at the same time, the secondary grinding used in the present invention is more conducive to improving the impurity removal efficiency than the primary grinding, avoiding insufficient removal of ductile impurities caused by the primary grinding, thereby affecting the electrochemical properties and cycle stability of the material, and is conducive to the recovery of waste lithium iron phosphate materials and the formation of sodium iron phosphate-based positive electrode materials with good electrochemical properties.
[0073] As a further solution, the molar ratio of elements in the sodium iron phosphate-based positive electrode precursor material in S4 is selected from Na:Fe:P as 3-y:2:3, y=0~0.01.
[0074] As a further solution, the weak acid solution in S3 is selected from one or more of carbonic acid, carboxylic acid, acetic acid, and citric acid; the weak acid solution within this range is conducive to effective etching on the material surface, maintaining the stability of the material structure, promoting the smooth leaching of lithium ions, and fully recovering lithium metal; and at the same time broadening the ion transmission channel to promote the stable adsorption of sodium ions.
[0075] As a further solution, the molar mass N of the hot saturated sodium carbonate solution in S3 is selected from N>0.7n; n is the molar mass of the waste lithium iron phosphate powder material. The excess hot saturated sodium carbonate solution can, on the one hand, promote the speed of sodium ion insertion and replacement after lithium ion leaching, and fully utilize the solid phase material to form a sodium iron phosphate core structure without an inert phase, and on the other hand, can fully remove the residual weak acid solution in the solid phase material to avoid its adverse effect on the subsequent formation of sodium iron phosphate material.
[0076] As a further solution, the solid-liquid separation method in S3 includes one or more of centrifugal separation, vacuum filtration, pressure filtration, and ultrafiltration;
[0077] As a further solution, the preparation method in S4 is one or more of spray drying, freeze drying, and sol-gel method;
[0078] Preferably, the preparation method in S4 is preferably a spray drying method; the spray drying method is easy to operate, can dry quickly, effectively prevent particle agglomeration, and form a uniform sodium iron phosphate-based positive electrode precursor material, thereby ensuring that the final prepared sodium iron phosphate-based positive electrode material has a higher ionic conductivity, thereby improving the capacity and coulombic efficiency of the battery material.
[0079] As a further solution, the sodium source in S4 is selected from one or more of sodium carbonate, sodium acetate, sodium citrate, sodium oxalate, and sodium bicarbonate; the iron source is selected from one or more of ferric phosphate, ferric chloride, ferric nitrate, and ferric sulfate; the phosphorus source is one or more of phosphoric acid, ammonium phosphate, diammonium hydrogen phosphate, and diammonium phosphate; by selecting suitable sodium source, iron source, and phosphorus source, it can be ensured that in the process of synthesizing sodium iron phosphate-based positive electrode precursor materials, the elements can be evenly mixed and reacted to form a uniform material structure, further optimizing the electrochemical properties of the material and improving its application effect in the battery.
[0080] As a further solution, the inert atmosphere in S5 is selected from one of argon and nitrogen atmospheres.
[0081] As a further solution, the heat treatment method in S5 is to undergo two heat treatment steps, the first heat treatment temperature is selected from 200-400°C, the heat treatment time is selected from 1 to 5 hours; the second heat treatment temperature is selected from 600 to 800°C, the heat treatment time is selected from 5 to 10 hours; the heating rate is selected from 5 to 10°C / min. A suitable heat treatment method can ensure that residual impurities such as moisture are fully removed, improve the crystallinity and purity of the material, and thus obtain a sodium iron phosphate-based positive electrode material with high conductivity, good cycle stability and capacity.
[0082] In a second aspect, the present invention provides a sodium iron phosphate-based positive electrode material, which is prepared by recycling the waste lithium iron phosphate material recycling process described in the first aspect.
[0083] The sodium iron phosphate-based positive electrode material provided by the present invention has an olivine-type sodium iron phosphate core structure material without an inert phase, has a stable sodium ion transmission channel, is conducive to the increase of sodium ion storage sites, and improves the sodium storage capacity and coulomb efficiency of the material; after the carbon source impregnating agent is infiltrated and coated, the sodium source, phosphorus source, and iron source are combined to form a sodium iron phosphate pyrophosphate mixed carbon shell structure on the surface of the sodium iron phosphate core material, and the layer structure has a uniform and dense conductive layer and has better conductivity; the sodium iron phosphate-based positive electrode material prepared thereby has a stable core-shell structure and exhibits excellent electrochemical performance and cycle stability. Since the positive electrode material is prepared by recycling waste lithium iron phosphate materials, it also has the dual advantages of environmental protection and economy and better electrochemical performance.
[0084] In a third aspect, the present invention provides a sodium iron phosphate-based positive electrode plate, wherein the positive electrode plate comprises the sodium iron phosphate-based positive electrode material of the second aspect, a conductive agent and a binder as described in the present invention.
[0085] The present invention has no particular restrictions on the type of conductive agent, as long as it has the function of enhancing the conductivity of the negative electrode and does not adversely affect the performance of the sodium iron phosphate-based positive electrode material. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As some specific examples, the conductive agent used to prepare the negative electrode plate can be selected from carbon blacks such as acetylene black and conductive carbon black, conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, polythiophene, tin oxide, zinc oxide and other metal oxide conductive agents and carbon nanofiber conductive agents, etc.
[0086] The present invention does not particularly limit the type of binder, as long as it has the effect of enhancing the adhesion between the negative electrode active material particles and does not adversely affect the performance of the sodium iron phosphate-based positive electrode material. Those skilled in the art can choose according to actual needs. As some specific examples, the binder used to prepare the negative electrode plate includes polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyimide, polystyrene sulfonic acid, polyacrylonitrile, polycarbonate or polyetherimide ketone, etc.
[0087] In a fourth aspect, the present invention provides a battery, the battery comprising the positive electrode sheet, the negative electrode sheet, the separator and the electrolyte described in the third aspect. The battery provided by the present invention comprises a sodium iron phosphate-based positive electrode material recycled and prepared by a waste lithium iron phosphate material recycling process, which not only has a low preparation method cost, a simple production process, and is green and pollution-free, but also has stable cycle performance, high ionic conductivity, and high sodium storage capacity and coulomb efficiency, and has important environmental significance in terms of material recycling, and points out a new direction for the recycling and reuse of waste lithium iron phosphate batteries and the preparation of sodium iron phosphate-based positive electrode materials; it can meet the needs of high-performance, environmentally friendly batteries in multiple fields, and has broad application prospects.
[0088] As a specific example of the implementation of the present invention, the detailed case is provided as follows:
[0089] Example 1
[0090] Discharging, disassembling, crushing and sorting the waste lithium iron phosphate batteries in sequence to obtain waste lithium iron phosphate powder materials;
[0091] 0.5g sodium carboxymethyl cellulose was added to 350g pure water and stirred until dissolved; 100g waste lithium iron phosphate powder material (with an Al content of 0.8% and a Cu content of 0.1%) was taken and added to the above mixed solution; then the mixture was transferred to a grinder together, and the first grinding was performed using 0.8mm zirconium oxide for 10 minutes, and then filtered with a 200-mesh filter to obtain a preliminary grinding slurry; at this time, a sample was taken, dried, and the Al content was measured to be 0.1% and the Cu content was 0.05%.
[0092] The above preliminary grinding slurry was transferred to 0.3mm zirconia for a second grinding for 10 minutes and then filtered with a 300-mesh filter to obtain a secondary grinding slurry; at this time, samples were taken, dried and tested, and the Al content was found to be 0.008% and the Cu content was 0.001%.
[0093] Add citric acid solution to the secondary grinding slurry, control the pH to 2.5, and continue to use 0.3mm zirconium oxide to grind until the powder particle size in the slurry is about 80nm. At this time, the lithium leaching rate is measured to be >99.95%. After centrifugal separation, lithium solution and solid phase are obtained, and traditional processes are used to recover lithium resources.
[0094] The solid phase was added to 93 g of hot saturated sodium carbonate solution and purified for 12 h. After centrifugation, 88 g of NaFePO was obtained. 4, Then, sodium carbonate, ammonium dihydrogen phosphate, and ferric phosphate mixed solution are mixed with the NaxFePO4 (to adjust the molar ratio of Na:Fe:P to (Na:Fe:P=3:2:3); the mixed solution is spray-dried, the inlet air temperature is set to 280°C, and the outlet temperature is maintained at 110°C to obtain a sodium iron phosphate-based positive electrode precursor material;
[0095] The sodium iron phosphate-based cathode precursor material was heat treated in a protective nitrogen atmosphere, firstly heated to 350 o C for 5 hours, then continue to heat up to 650 o C reaction for 10 h to obtain a sodium iron phosphate-based cathode material with a core-shell structure.
[0096] Example 2
[0097] The specific implementation steps are the same as those in Example 1, except that: 0.7 g of sodium carboxymethyl cellulose is added to 350 g of pure water and stirred until dissolved; 100 g of waste lithium iron phosphate powder material (wherein the Al content is 0.8% and the Cu content is 0.1%) is taken; and added to the above mixed solution; then they are transferred to a grinder together, and a first grinding is performed using 0.8 mm zirconium oxide for 10 min, and then filtered with a 200-mesh filter to obtain a preliminary grinding slurry; at this time, a sample is taken, dried, and the Al content is measured to be 0.11% and the Cu content is 0.06%.
[0098] Example 3
[0099] The specific implementation steps are the same as those in Example 1, except that: 0.5 g of sodium lignin sulfonate is added to 350 g of pure water and stirred until dissolved; 100 g of waste lithium iron phosphate powder material (wherein the Al content is 0.8% and the Cu content is 0.1%) is taken; and added to the above mixed solution; then they are transferred to a grinder together, and a first grinding is performed using 0.8 mm zirconium oxide for 10 min, and then filtered with a 200-mesh filter to obtain a preliminary grinding slurry; at this time, a sample is taken, dried, and the Al content is measured to be 0.14% and the Cu content is 0.08%.
[0100] Example 4
[0101] The specific implementation steps are the same as those in Example 1, except that: 0.4 g of sodium carboxymethyl cellulose is added to 350 g of pure water and stirred until dissolved; 100 g of waste lithium iron phosphate powder material (wherein the Al content is 0.8% and the Cu content is 0.1%) is taken; and added to the above mixed solution; then they are transferred to a grinder together, and a first grinding is performed using 0.8 mm zirconium oxide for 10 min, and then filtered with a 200-mesh filter to obtain a preliminary grinding slurry; at this time, a sample is taken, dried, and the Al content is measured to be 0.12% and the Cu content is 0.07%.
[0102] Example 5
[0103] The specific implementation steps are the same as those in Example 1, except that: a 0.8 mm tungsten carbide-based cemented carbide is used for the first grinding for 10 minutes and then filtered with a 200-mesh filter to obtain a preliminary grinding slurry; at this time, a sample is taken and dried, and the Al content is measured to be 0.13% and the Cu content is 0.06%.
[0104] Example 6
[0105] The specific implementation steps are the same as those in Example 1, except that: the first grinding is performed using 1 mm zirconium oxide for 10 minutes and then filtered with a 200-mesh filter to obtain a preliminary grinding slurry; at this time, a sample is taken and dried, and the Al content is measured to be 0.13% and the Cu content is 0.05%.
[0106] Example 7
[0107] The specific implementation steps are the same as those in Example 1, except that: citric acid solution is added to the secondary grinding slurry, the pH is controlled to 2.5, and 0.3 mm zirconium oxide is continued to be ground until the powder particle size in the slurry is about 180 nm. At this time, the lithium leaching rate is measured to be greater than 99.92%. After centrifugal separation, a lithium solution and a solid phase are obtained, and lithium resources are recovered using traditional processes.
[0108] Example 8
[0109] The specific implementation steps are the same as those in Example 1, except that: citric acid solution is added to the secondary grinding slurry, the pH is controlled to 2.5, and 0.3 mm zirconium oxide is continued to be ground until the powder particle size in the slurry is about 120 nm. At this time, the lithium leaching rate is measured to be greater than 99.91%. After centrifugal separation, a lithium solution and a solid phase are obtained, and lithium resources are recovered using traditional processes.
[0110] Example 9
[0111] The specific implementation steps are the same as those in Example 1, except that: a carbonate solution is added to the secondary grinding slurry, the pH is controlled to be 2.5, and 0.3 mm zirconium oxide is continued to be ground until the powder particle size in the slurry is about 80 nm. At this time, the lithium leaching rate is measured to be greater than 99.94%. After centrifugal separation, a lithium solution and a solid phase are obtained, and lithium resources are recovered using traditional processes.
[0112] Example 10
[0113] The specific implementation steps are the same as those in Example 1, except that: a carboxylic acid solution is added to the secondary grinding slurry, the pH is controlled to 2.5, and 0.3 mm zirconium oxide is continued to be used for grinding until the powder particle size in the slurry is about 80 nm. At this time, the lithium leaching rate is measured to be greater than 99.97%. After centrifugal separation, a lithium solution and a solid phase are obtained, and lithium resources are recovered using traditional processes.
[0114] Comparative Example 1
[0115] The specific implementation steps are the same as those in Example 1, except that sodium carboxymethyl cellulose is not added, and the preliminary grinding slurry is sampled and dried, and the Al content is measured to be 0.5%, and the Cu content is 0.08%; the above preliminary grinding slurry is transferred to 0.3 mm zirconium oxide for a second grinding for 10 minutes, and then filtered with a 300 mesh filter to obtain a secondary grinding slurry; at this time, sampling is taken, dried and tested, and the Al content is 0.4%, and the Cu content is 0.05%.
[0116] Comparative Example 2
[0117] The specific implementation steps are the same as those in Example 1, except that 0.5 g of sodium hexametaphosphate is added to 350 g of pure water and stirred until dissolved; 100 g of waste lithium iron phosphate powder material (wherein the Al content is 0.8% and the Cu content is 0.1%) is taken; added to the above mixed solution; then transferred to a grinder together, the first grinding is performed using 0.8 mm zirconium oxide for 10 minutes, and then filtered with a 200-mesh filter to obtain a preliminary grinding slurry; at this time, a sample is taken, dried, and the Al content is measured to be 0.18% and the Cu content is 0.08%.
[0118] The above preliminary grinding slurry was transferred to 0.3mm zirconia for a second grinding for 10 minutes and then filtered with a 300-mesh filter to obtain a secondary grinding slurry; at this time, samples were taken, dried and tested, and the Al content was found to be 0.009% and the Cu content was 0.008%.
[0119] Comparative Example 3
[0120] The specific implementation steps are the same as those in Example 1, except that only the first grinding is performed, using 0.3 mm zirconium oxide for grinding for 30 minutes, and the slurry is passed through a 300-mesh sieve. At this time, samples are taken and dried, wherein the Al content is 0.058% and the Cu content is 0.034%.
[0121] Comparative Example 4
[0122] The specific implementation steps are the same as those in Example 1, except that the above-mentioned preliminary grinding slurry is transferred to 0.3 mm zirconia for a second grinding for 10 minutes and then filtered with a 300-mesh filter to obtain a secondary grinding slurry; at this time, sampling, drying and testing, the Al content is 0.035%, and the Cu content is 0.022%.
[0123] Add citric acid solution to the secondary grinding slurry, control the pH to 2.5, and continue to use 0.1mm zirconium oxide to grind until the powder particle size in the slurry is about 80nm. At this time, the lithium leaching rate is measured to be >99.9%. After centrifugal separation, lithium solution and solid phase are obtained, and traditional processes are used to recover lithium resources.
[0124] Comparative Example 5
[0125] The specific implementation steps are the same as those in Example 1, except that the above-mentioned preliminary grinding slurry is transferred to 2mm zirconia for a second grinding for 10 minutes and then filtered with a 300-mesh filter to obtain a secondary grinding slurry; at this time, samples are taken, dried and tested, and the Al content is 0.1% and the Cu content is 0.08%.
[0126] Add citric acid solution to the secondary grinding slurry, control the pH to 2.5, and continue to use 1.5mm zirconium oxide to grind until the powder particle size in the slurry is about 80nm. At this time, the lithium leaching rate is measured to be >99.9%. After centrifugal separation, lithium solution and solid phase are obtained, and traditional processes are used to recover lithium resources.
[0127] Comparative Example 6
[0128] The specific implementation steps are the same as those in Example 1, except that: ammonium hydroxide solution is added to the secondary grinding slurry, the pH is controlled to 9.5, and 0.3 mm zirconium oxide is continued to be ground until the powder particle size in the slurry is about 80 nm. At this time, the lithium leaching rate is measured to be greater than 99.9%. After centrifugal separation, a lithium solution and a solid phase are obtained, and lithium resources are recovered using traditional processes.
[0129] Comparative Example 7
[0130] The specific implementation steps are the same as those in Example 1, except that the solid phase is added to 93 g of hot saturated sodium hydroxide solution and purified for 12 hours.
[0131] Comparative Example 8
[0132] The specific implementation steps are the same as those in Example 1, except that: the solid phase material is directly mixed with sodium carbonate, ammonium dihydrogen phosphate, iron phosphate mixed solution and NaxFePO4 (to adjust the molar ratio of Na:Fe:P to (Na:Fe:P=3:2:3); the mixed solution is spray-dried, the inlet air temperature is set to 280°C, and the outlet temperature is maintained at 110°C to obtain a sodium iron phosphate-based positive electrode precursor material;
[0133] Specific test conditions and methods:
[0134] Purpose of the experiment: To test the electrochemical performance of the sodium iron phosphate-based positive electrode materials prepared in the examples and comparative examples of the present invention, and to repeat 5 groups of experiments in parallel and take the average value.
[0135] Experimental method: The positive electrode slurry was prepared by mixing active material: conductive agent: binder = 7:2:1, and coated on aluminum foil to prepare the positive electrode. Glass fiber was used as the separator and sodium sheet was used as the negative electrode. CR2032 button half-cell was made under the condition that the water and oxygen values in the glove box were less than 0.01ppm. The test was carried out on a Xinwei electrochemical tester. The performance test was carried out for 300 cycles at a constant current of 1C. The rate performance was cycled for 5 cycles at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, and 20C, respectively.
[0136] Reversible specific capacity test: The cyclic test procedure is set on the Xinwei electrochemical tester as follows: stand for 8 hours, charge to 4.3V at constant current, discharge to 1.5V at constant current, stand for 5 minutes, and end the test after 300 cycles at 1C.
[0137] The first-cycle coulomb efficiency is the ratio of the first-cycle discharge specific capacity to the charge specific capacity.
[0138] Impurity content test: Use inductively coupled plasma emission spectrometer (ICP) to test the content of impurities (aluminum and copper) in lithium iron phosphate powder.
[0139]
[0140] Through the data in Table 1 and Examples 1-10 and Comparative Examples 1-8, we can see that the sodium iron phosphate-based positive electrode material prepared by optimizing the recycling process of waste lithium iron phosphate materials in the present invention has higher reversible specific capacity, first-cycle efficiency and capacity retention rate at high rates. This shows that the present invention can effectively remove ductile impurities by adding carbon source wetting agents to graded grinding methods for waste lithium iron phosphate materials, and combine acid treatment lithium leaching and saturated sodium carbonate sodium supplementation to fully recover lithium and achieve the effect of dual construction materials, effectively broaden the ion transmission channel, and further prepare sodium iron phosphate-based positive electrode materials with excellent electrochemical properties; it is of great significance to achieve efficient utilization of resources and promote sustainable development in view of the problem of comprehensive component recovery of waste lithium iron phosphate batteries in a low-cost, safe and convenient manner.
[0141] It can be seen from Examples 1-10 and Comparative Example 1 that the sodium iron phosphate-based positive electrode material prepared by graded grinding with the addition of a wetting agent has better electrochemical properties. This is because the addition of a wetting agent helps to reduce the agglomeration phenomenon between particles, so that the ductile impurities are fully exposed during the grinding process, the impurities are effectively removed, and the embedding sites of sodium ions are increased, thereby increasing the transmission path of sodium ions, improving the capacity and coulombic efficiency of the battery, and avoiding the formation of an inert phase during the subsequent preparation of the sodium iron phosphate-based positive electrode material that affects the electrochemical performance of the battery.
[0142] By combining Example 1 with Comparative Example 2 Figure 8 , Figure 6 As can be seen from the data in Table 1, Comparative Example 2 does not use a carbon source wetting agent, and its rate capacity at 20C is significantly lower than that of Example 1. This reflects that the wetting agent used in Example 1 can also serve as a carbon source, further providing a carbon source for the sodium iron pyrophosphate shell structure, and is fully dispersed through its own grinding function to form a uniform and dense conductive layer, thereby further improving the rate performance of the battery.
[0143] It can be seen from Example 1 and Comparative Example 3 that Comparative Example 3 was ground only once and then continued with the subsequent steps. It was measured that the Al and Cu contents after grinding were high, and the electrochemical properties such as the rate and cycle stability were poor. This is because it is difficult to fully and effectively remove ductile impurities such as Al and Cu by grinding once. The presence of impurities is not conducive to forming a uniform and unobstructed ion transmission path, blocking the ion transmission channel, and increasing the interface impedance, which is not conducive to the formation of an olivine-type sodium iron phosphate core material without an inert phase, and reduces the coulombic efficiency, capacity, rate and other performance of the battery.
[0144] It can be seen from Examples 1-10 and Comparative Examples 4 and 5 that when Examples 1-10 are ground with a suitable grinding diameter, it is beneficial to fully crush the waste lithium iron phosphate powder material, expose the ductile impurities and effectively remove them, and improve the purity of the material; Comparative Example 4 uses an overly small grinding medium diameter, which will cause the ductile impurities to be mixed in at the initial stage of grinding, and the grinding medium diameter of Comparative Example 5 is too large, which is not conducive to fully opening the waste lithium iron phosphate powder material, and both will cause impurity residues, affect the stable and smooth embedding of sodium ions, reduce structural stability, and increase ion transport obstacles during charging and discharging, thereby reducing the coulombic efficiency, rate and cycle stability of the battery.
[0145] It can be seen from Example 1 and Comparative Example 6 that when Comparative Example 6 uses an alkaline solution for lithium leaching, although the leaching rate of lithium ions is still high, the electrochemical performance of the final battery is low. This is because the alkaline solution is used for treatment, and the impurities cannot be effectively removed when the hot saturated sodium carbonate solution is used to supplement sodium, causing impurities to remain, thereby affecting the battery capacity and rate performance, and failing to react with the hot saturated sodium carbonate solution to generate CO2 gas to further broaden the ion transmission channel, thereby improving the electrochemical performance of the battery.
[0146] It can be seen from Example 1 and Comparative Example 7 that although sodium hydroxide solution is used for sodium supplementation in Comparative Example 7, the performance of the battery finally prepared is still lower than that of Example 1. This is because the sodium hydroxide solution is also unable to react with the weak acid solution remaining during lithium immersion to generate CO2 gas to further expand the voids in the crystal structure, thereby reducing the insertion and supplementation rate of sodium ions, thereby reducing the coulombic efficiency and other performance of the battery.
[0147] It can be seen from Example 1 and Comparative Example 8 that in Example 1, the solid phase material is first subjected to sodium supplementation treatment, which can remove residual weak acid solution on the one hand, and prevent side reactions from occurring during subsequent heat treatment that affect material stability and electrochemical properties; on the other hand, a sodium iron phosphate core material with an olivine structure without an inert phase is formed by sodium supplementation treatment and recombination of the phosphorus-iron framework, and then secondary coating with a sodium source, a phosphorus source, and an iron source is performed to form a sodium iron phosphate-based positive electrode material having both good conductivity and high stability; while in Comparative Example 8, the solid phase material after lithium immersion is directly treated with a sodium source, a phosphorus source, and an iron source to prepare a sodium iron phosphate pyrophosphate material, which will increase side reactions during the heat treatment process, reduce structural stability, and thus destroy ion transport channels, which is not conducive to the stable adsorption of sodium ions in the solid phase material, so the ion transport efficiency is low, the cycle stability is poor, and the measured electrochemical properties are lower than those of Example 1.
[0148] Through Examples 1-6 and Examples 7-8 and combined with Table 1 and Figure 6 , Figure 7It can be seen from the data that Examples 1-6 have better first-cycle coulombic efficiency and cycle retention rate, which indicates that the powder particle size in the optimized range is more conducive to the embedding of lithium ions, obtains a suitable pore size change, promotes the embedding efficiency of sodium ions, maintains the stable embedding of sodium ions, reduces the interface resistance, and facilitates the formation of a stable and smooth ion transmission path, thereby having higher coulombic efficiency and cycle stability.
[0149] pass Figure 1 , 2 3 It can be seen that graded sand grinding can break up the agglomerated lithium iron phosphate particles and the coating of the surface carbon layer, which is more conducive to the leaching rate of lithium elements > 99.9% under weak acid conditions; it is convenient for sodium elements to fill in the position and avoid the production of inert phase sodium iron phosphate in the preparation of sodium iron phosphate.
[0150] pass Figure 4 , Figure 5 It can be seen from the XRD that after the nano-lithium iron phosphate is immersed in lithium, an excess of hot saturated solution is used to obtain the first layer of sodium iron phosphate core, and through secondary synthesis, a core-shell structure of sodium iron pyrophosphate with better conductivity and improved structural stability is obtained.
[0151] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A recycling process for waste lithium iron phosphate materials, the specific steps comprising: S1: adding waste lithium iron phosphate powder material to pure water containing a carbon source wetting agent, performing a first grinding with a grinding medium and filtering to remove ductile impurities to obtain a preliminary grinding slurry, wherein the average particle size of the powder in the preliminary grinding slurry is 1-3 μm; The ductile impurity content meets 0%-0.3%; S2: Grind the preliminary grinding slurry described in S1 for a second time through a grinding medium, and then filter to remove ductile impurities to obtain a secondary grinding slurry. At this time, the average particle size of the powder in the secondary grinding slurry is 0.05-0.8 μm. The secondary grinding slurry is tested for ductile impurity content to ensure that the ductile impurity content meets 0-0.01% before proceeding to the next operation step; wherein the ductile impurity content refers to the percentage of the mass of the ductile impurities to the mass of the measured slurry after drying; S3: Add excess weak acid solution to the secondary grinding slurry in S2 to treat it, so that lithium is leached out. After solid-liquid separation, the solid phase material is added to excess hot saturated sodium carbonate solution to react and obtain sodium iron phosphate Na x FePO4; wherein x is selected from 0.9-1.05; S4: Mix the sodium source, phosphorus source, iron source and the sodium iron phosphate Na described in S3 x FePO4 was mixed to prepare a sodium iron phosphate-based positive electrode precursor material; S5: heat-treating the sodium iron phosphate-based positive electrode precursor material described in S4 under an inert gas atmosphere to obtain a sodium iron phosphate-based positive electrode material.
2. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The amount of the carbon source impregnating agent added in S1 accounts for 0.2%-1% of the amount of the waste lithium iron phosphate powder material added, and the amount of the waste lithium iron phosphate powder material added in S1 accounts for 20%-40% of the mass of the pure water.
3. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The average particle size of the powder in the secondary grinding slurry in S2 is 0.05-0.1 μm.
4. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The ductile impurities include one or more metal elements of Cu, Al, Sn, S, Ni, and Co; the carbon source wetting agent in S1 includes one or more of sodium carboxymethyl cellulose, sodium lignin sulfonate, and sodium dodecyl sulfate; the grinding media in S1 and S2 include one or more of tungsten steel grinding media, cemented carbide grinding media, ceramic grinding media, and glass grinding media.
5. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The grinding media in S1 and S2 are ceramic grinding media.
6. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The diameter of the grinding medium in S1 is greater than the diameter of the grinding medium in S2; the mesh size of the filter screen in S1 is less than the mesh size of the filter screen in S2; and the grinding time in S1 and S2 is 10-30 minutes.
7. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The diameter of the grinding medium in S1 is 0.8-1.5 mm, and the mesh number of the filter screen is 100-200 meshes; the diameter of the grinding medium in S2 is 0.1-0.7 mm, and the mesh number of the filter screen is 300-500 meshes.
8. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The molar ratio of elements of the sodium iron phosphate-based positive electrode precursor material in the S4 is selected from Na:Fe:P, which is 3-y:2:3; y=0~0.01; the preparation method in the S4 is one or more of spray drying, freeze drying, and sol-gel method; the sodium source in the S4 is selected from one or more of sodium carbonate, sodium acetate, sodium citrate, sodium oxalate, and sodium bicarbonate; the iron source is selected from one or more of iron phosphate, ferric chloride, ferric nitrate, and ferric sulfate; the phosphorus source is one or more of phosphoric acid, ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
9. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The preparation method in S4 is spray drying.
10. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The weak acid solution in S3 is selected from one or more of carbonic acid, carboxylic acid, acetic acid, and citric acid; the molar mass N of the hot saturated sodium carbonate solution in S3 is selected from N>0.7n; n is the molar mass of the waste lithium iron phosphate powder material; the solid-liquid separation method in S3 includes one or more of centrifugal separation, vacuum filtration, pressure filtration, and ultrafiltration.
11. The process for recycling waste lithium iron phosphate materials according to claim 1, characterized in that: The inert atmosphere in S5 is selected from one of argon or nitrogen atmosphere; the heat treatment method in S5 is to undergo two heat treatment steps, the first heat treatment temperature is selected from 200-400°C, and the heat treatment time is selected from 1 to 5h; the second heat treatment temperature is selected from 600 to 800°C, and the heat treatment time is selected from 5 to 10h; the heating rate is selected from 5 to 10°C / min.
12. A sodium iron phosphate-based positive electrode material, characterized in that: The sodium iron phosphate-based positive electrode material is prepared by recycling the waste lithium iron phosphate material by the recycling process described in any one of claims 1-11.
13. A sodium iron phosphate-based positive electrode plate, characterized in that: The sodium iron phosphate-based positive electrode plate comprises the sodium iron phosphate-based positive electrode material according to claim 12, a conductive agent and a binder.
14. A battery comprising the sodium iron phosphate-based positive electrode sheet, negative electrode sheet, separator and electrolyte according to claim 13.
Citation Information
Patent Citations
Recycling and regenerating method of lithium iron phosphate battery positive electrode plate leftover materials
CN112658000A
Method for recovering lithium from lithium iron phosphate waste and application thereof
CN112678791A